Dos Direitos Humanos à Gestão Socioambiental Brasileira : uma análise de conjuntura da agenda 2030 a partir das conferências internacionais Rio-92 e Rio+20 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The purpose of this Master's Thesis is to carry out an Analysis of the Global Agenda 2030 in Brazil, based on the RIO-92 and RIO + 20 Conferences. Of fundamental link between the concept of Sustainability and the effectiveness of Human Rights, Agenda 2030 enshrines in its 17 SDGs and 169 goals, a mechanism for mutual cooperation, requiring cross-cutting measures in the actions of countries ranging from apparatus measures to reduction of poverty, environmental preservation until the achievement of world peace until the year 2030. The time frame of the chosen Analysis is from the year of creation of the 2030 Agenda, that is, 2015 until the year of 2019. To this end, four specific objectives in pursuing the topic at hand. The first objective is based on identifying the structural links between Human Rights and the origin of Sustainability, the creation of the goals and objectives of Agenda 2030, as an instrument of environmental protection and preservation. Therefore, the respective methodology is materialized through bibliographic, documentary research and Analysis of the Situation, with the mission of exercising the necessary dynamism in the development of this research. As a result, it can be highlighted that the Agenda 2030 represents an ambitious goals project walking slowly in Brazil, since, in terms of governance, the country remains extremely influenced by ingrained developmentism since the 20th century, clearly demonstrating their difficulties in transforming sustainable speeches into governmental practice, in urgent need of changes. That is, if there is no integration in the planning and development of public policies in the country and the integration between all the social actors involved, from the Federal Government to civil society in the implementation of the 2030 Agenda, it is unlikely that a scenario different from the current one will be built in the next one. In other words, we have sufficient mechanisms for change, but there is a lack of awareness and cooperation so that the beauty of the speeches will come to live in the practice of governance in all its spheres, reaching the goals and objectives towards sustainable progress.
Keywords: Análise de Conjuntura; Agenda 2030; Direitos Humanos; Sustentabilidade; Rio-92 e Rio+20; Conjuncture Analysis; Agenda 2030; Sustainability; Human Rights; Rio-92 and Rio+20; CNPQ::CIENCIAS SOCIAIS APLICADAS